Magneto-Gravimetric Separation of Nonmagnetic Solids (eb219ab0-6ac3-44c1-8e8c-189ca234ca9d) - S. E. Khalafalla; G. W. Reimers (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1974)
A colloidal solution of a ferrimagnetic material, such as magnetite, in a liquid that is immiscible with and lighter than water is projected for use in selective separation of particles according to their density spectrum. Magnetic levitation forces can be created as an antigravity field when the fluid is properly placed in an inhomogeneous magnetic field. When the gradient of the magnetic field is directed downwards, the levitation force in the fluid will be in an upward direction to float sinking nonmagnetic bodies by counterbalancing their density mismatch with the magnetic fluid. Several nonmagnetic objects with densities ranging from 2.50 to 11.35-g cm' were made to float or submerge at will in a 0.96-g cm' density fluid placed in vertical magnetic field gradients ranging from 0.1 to 1 kilo-oersted cm-'. The magnetic levitation force in dyne cm' was found to vary linearly as a function of the object-fluid density mismatch with a slope equal to one g, the acceleration due to gravity.